Wood characterization of Salix. 2: Relationships between optical and other wood properties - Villegas, M. S.; Area, M. C. (Forest Systems, 2009)
The objective of this study was to establish relationships between some characteristics of the wood of Salix and their possible influence on its optical properties. In both willow clones, the presence of stains caused the decrease of brightness, L*, and b*. This effect was intensified in the more deteriorated areas. Tyloses increased with the presence of such stains. The whiter wood showed the highest values of L*, being more yellow and less red, except for the "dark zone" in the American willow, and the "brown stains" and the "blue stain" in the hybrid willow, in which the parameters a* and b* correlated positively. The presence of defects in the wood was related to the decrease of density in both clones, except for the "dark-brown stain" in the American willow, which caused the increase of disks density when presenThe content of insoluble and total lignin correlated negatively with brightness and L* in American willow, and with basic density in the hybrid. In the last clone, the extractives in hot water and alcohol-benzene, correlated with the alkalisoluble substances content (frequently used as a measure of decay degree), and also played an important role in determining the tendency to blue color in the stains of the wood.